(untitled) (Journal of Universal Excellence, 2026)
Research Question (RQ): What is the distribution of the most common disease groups according to the International Classification of Diseases ICD-10-AM (version 11) by gender and age groups among cases of long- term sick leave (LTSL) exceeding 42 and 365 days in the years 2021 to 2023? Purpose: The aim of the study is to identify disease groups under ICD-10-AM (version 11) that are most frequently associated with long-term sick leave exceeding 42 and 365 days in the working population. Method: The research combines a descriptive method for literature review and a quantitative method for statistical analysis of data from the databases of the National Institute of Public Health of the Republic of Slovenia (NIJZ, RS). This allows for a systematic and in-depth understanding of LTSL beyond 42 and 365 days. Results: The analysis of LTSL during 2021–2023, which included cases of absences longer than 42 and 365 days classified by gender, age group, and disease group according to ICD-10-AM (version 11), revealed several findings. Among women under the age of 40, the most common reasons for LTSL beyond 42 days were related to pregnancy, childbirth, and the postpartum period. In older age groups, i.e., women aged 41 and above, diseases of the musculoskeletal system and connective tissue emerged as the most common causes for both LTSL over 42 and over 365 days. Among younger men and men up to the age of 54, injuries and poisonings outside the workplace were the most frequent reasons for LTSL over 42 days. These were followed by musculoskeletal and connective tissue diseases, which were also associated with the longest absences, exceeding 365 days. Organization: Properly structured work organization represents a key factor in reducing risks for LTSL, especially in the context of chronic non-communicable diseases, work overload, unfavorable working conditions, and lack of adequate workplace support. Society: Only through cooperation between employers, employees, and the broader society can sustainable improvements in the health of the working population be achieved, while reducing the financial and social consequences of LTSL. Originality: This study on LTSL, disaggregated by gender, ICD-10-AM (version 11) disease groups, and age groups, provides an important scientific contribution to the comprehensive understanding of the causal factors affecting LTSL. It reflects a systematic and multidimensional analytical approach that integrates demographic, epidemiological, and temporal aspects, as well as the definition of different LTSL thresholds, including absences longer than 42 and 365 days. Limitations/Further Research: The study covers a three-year period and examines LTSL, defined by thresholds of over 42 and 365 days. Extending the timeframe and including leading diagnoses within ICD-10 AM (version 11) disease groups would allow for more precise identification of specific diagnoses and better detection of long-term trends.